2020
DOI: 10.1080/09540121.2020.1748559
|View full text |Cite
|
Sign up to set email alerts
|

The association between severe menopausal symptoms and engagement with HIV care and treatment in women living with HIV

Abstract: Using data from the PRIME Study, an observational study of the menopause in women living with HIV in England, we explored the association between menopausal symptoms and: (i) antiretroviral therapy (ART) adherence and (ii) HIV clinic attendance.We measured menopausal symptom severity with the Menopause Rating Scale (MRS, score ≥17 indicating severe symptoms), adherence with the CPCRA Antiretroviral Medication Adherence Self-Report Form, and ascertained HIV clinic attendance via self-report. Odds ratios were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 18 publications
0
25
0
1
Order By: Relevance
“…3 Only a few studies have specifically examined the association between menopausal symptoms and adherence to antiretroviral therapy (ART). [4][5][6][7] A recent analysis of the Positive Transitions through the Menopause (PRIME) study, a cross-sectional study of women living with HIV in the UK aged 45-60 years, reported a significant association between severe menopausal symptoms and both sub-optimal adherence and HIV clinic attendance. 7 Despite the significant impact of sub-optimal adherence and poor clinic attendance on clinical outcomes, 8,9 there are currently no clear data on whether clinical HIV outcomes change among women as they progress through different stages of the menopause.…”
Section: Introductionmentioning
confidence: 99%
“…3 Only a few studies have specifically examined the association between menopausal symptoms and adherence to antiretroviral therapy (ART). [4][5][6][7] A recent analysis of the Positive Transitions through the Menopause (PRIME) study, a cross-sectional study of women living with HIV in the UK aged 45-60 years, reported a significant association between severe menopausal symptoms and both sub-optimal adherence and HIV clinic attendance. 7 Despite the significant impact of sub-optimal adherence and poor clinic attendance on clinical outcomes, 8,9 there are currently no clear data on whether clinical HIV outcomes change among women as they progress through different stages of the menopause.…”
Section: Introductionmentioning
confidence: 99%
“…Menopausal symptoms may undermine ART adherence [ 18 , 43 ]. In this study, women had good level of adherence and a good immunological status.…”
Section: Discussionmentioning
confidence: 99%
“…Menopausal status was self-reported, as, in other similar published studies [ 9 , 11 , 22 , 23 ], and was categorized as: pre-menopausal, if a woman had regular menstruation; peri-menopausal, if a woman reported amenorrhea for at least three months in the previous year; and post-menopausal, if a woman had 12 consecutive months of amenorrhea. Women who had a history of hysterectomy and/or bilateral oophorectomy were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…1 Among women living with HIV, menopausal symptoms are associated with psychological distress 1 and decreased adherence to ART (which is important in terms of women’s own health and also the prevention of HIV transmission to others). 5 Use of systemic and topical hormone replacement therapy (HRT) is very low among women living with HIV (8% and 3%, respectively) despite the high prevalence of symptoms. 1 …”
Section: What Is the Impact Of The Menopause On Women Living With Hiv?mentioning
confidence: 99%
“…Among women living with HIV, menopausal symptoms are associated with psychological distress 1 and decreased adherence to ART (which is important in terms of women’s own health and also the prevention of HIV transmission to others). 5…”
Section: What Is the Impact Of The Menopause On Women Living With Hiv?mentioning
confidence: 99%